Ben Downing: Queen Bee of Tuscany: The Redoubtable Janet Ross - Jaine, Tom (Petits Propos Culinaires, 2014)
Ben Downing: Queen Bee of Tuscany: The Redoubtable Janet Ross: Farrar, Strauss and Giroux, 2013: 340 pp., hardback, £22.85.